2021
DOI: 10.3390/ijms23010228
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Transport Characteristics of PdCu–Nb–PdCu Membranes Modified with Nanostructured Palladium Coating

Abstract: A method for obtaining composite gas-diffusion PdCu–Nb–PdCu membranes modified with a nanostructured crystalline coating was developed to increase the performance of Nb-based membranes. A modifying functional layer with a controlled size and composition was synthesized by electrochemical deposition, which made it possible to determine a certain geometric shape for palladium nanocrystallites. Developed PdCu–Nb–PdCu membranes have demonstrated flux values up to 0.232 mmol s−1 m−2 in the processes of diffusion pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Palladium membranes are most preferred in industrial hydrogen separation conditions. [ 10 , 11 , 12 ]. This is due to the high ability of palladium to transport hydrogen in a wide temperature range, due to the higher solubility and diffusion ability of the FCC lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Palladium membranes are most preferred in industrial hydrogen separation conditions. [ 10 , 11 , 12 ]. This is due to the high ability of palladium to transport hydrogen in a wide temperature range, due to the higher solubility and diffusion ability of the FCC lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles with certain facets and shapes differ from bulk materials in terms of thermal, optical, electrical, and magnetic aspects due to their unique morphology and size effects. This makes them promising materials in the field of catalysis [1,2], spectroscopy [3], nanomedicine [4,5], electronics [6,7], energy conversion [8], and hydrogen energy, including high-purity hydrogen evolution (99.999% purity) [9][10][11][12], etc. The branch of synthesis of functional nanostructured coatings with a greater specific active surface area and improved catalytic, protective, and other necessary properties is of great interest [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that hydrogen permeability of membranes increased after each stage, as the use of the air heat treatment technique directly affected the increase in the effective surface area of the membrane. Another way to activate the membrane surface is its modification with powdered catalytically active particles [33][34][35][36]. The most promising way is the application of nanoparticles, which have become widespread in many areas of science and industry due to the unusual physical and chemical properties of nanoparticles [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%